Correlation of Ankle-Brachial Index with Diabetic Retinopathy in Patients of Type 2 Diabetes: ABI and diabetic retinopathy - mazhar, Abdullah; malik, tayyaba gul; ali, aalia; Nadeem, Hina (Pakistan Journal of Ophthalmology, 2020)
Objectives: To find out a relationship of diabetic retinopathy with ankle-brachial (ABI) in patients of type 2 diabetes. Material and Methods It was a cross-sectional observational study carried out in Arif Memorial Teaching hospital and Rashid Latif Medical College from January 2019 to June 2019. 120 patients were selected by purposive convenient sampling from outpatient department of Arif Memorial Teaching hospital. After clinical history, complete ocular examination was performed. Random blood sugar levels were measured using Glucometer. Ankle-brachial index was calculated by dividing the systolic pressure at ankle by the systolic blood pressure at arm. Statistical analysis was done using SPSS 25. Independent sample t test and chi square tests were used to find out the significance of the results. Results: In this study of 120 diabetic patients, 80 (66.7%) were female and 40 (33.3%) were males. Mean Ankle Branchial Index (ABI) of Males was 0.96±0.11 and for females was 0.97±0.14. Among 120 participants of this study, 73 (60.83 %) patients had no signs of diabetic retinopathy, 35 (29.16 %) patients had NPDR and 12 (10%) patients had PDR. ABI was not associated with gender and duration of diabetes. However, there was negative and weak linear relationship between BSR and ABI (r= -0.221). This correlation was higher in diabetics of less than 5 year duration (r=-0.286) than in patients of more than 5 years duration of diabetes (r=-0.129). Conclusion: Our study indicates that ABI is not significantly related with diabetic retinopathy. However, there is a positive relationship of ABI with high blood sugar levels.